PENGARUH SUBSITUSI AMPAS TEBU PADA FLY ASH TERHADAP KUAT TEKAN MORTAR GEOPOLIMER - Saputra, Ksatria; Mulyati, Ely; Firdaus (Universitas Muhammadiyah Sorong, 2024)
Geopolymer mortar is an alternative material to replace Indonesian portland cement. Made from a mixture of rice husk ash and fly ash without using cement, utilizes industrial waste and is environmentally friendly. This study analyzes the effect of sugarcane bagasse substitution on mortar setting time and compressive strength of geopolymer mortar in fly ash-based mixtures. The benefits include increasing the additional value of bagasse fly ash as a mixture and reducing the use of cement material in mortar. Become a reference for other researchers. This research shows that the results of the substitution of bagasse for fly ash have an effect on the hardening time and strength of the mortar. The hardening time meets the standards for initial sett, but not for final sett. The greatest effect occurred at a percentage of 15% with an initial set hardening time of 90 minutes and a final set of 135 minutes. Mortar strength continues to increase from 7 days to 28 days at each percentage, with the highest value at the 15% percentage of 10.4 Mpa.